Geothermal investigations in western Anatolia using equilibrium temperatures from shallow boreholes - ERKAN, KAMİL (COPERNICUS GESELLSCHAFT MBH, 2015)
Determination of the conductive heat flow in western Anatolia has broad implications in many areas, including studies on the present-day extensional tectonic activity and assessments of the geothermal resources in the region. In this study, high-resolution equilibrium temperatures from 113 boreholes with depths of similar to 100 m were analyzed for determination of the conductive heat flow. Thermal conductivities were either determined by measurements on outcrops or estimated using lithologic records. By a detailed analysis of temperature-depth curves, a total of 55 sites were selected as being useful for further conductive gradient/heat flow calculations, while the remaining 58 sites were abandoned due to hydrological effects on temperatures. Heat flow values with formal errors were calculated for 24 sites where rock thermal conductivity information is available. Due to the shallow depths of the investigated boreholes and uncertainties in thermal conductivity information, the results include a large accumulated error. A preliminary heat flow map is generated using the results of this study and a previous study in the southern Marmara region. Elevated heat flow values of 85-95 mW m(-2) are observed in the coastal areas, including peninsular parts of Canakkale and Izmir. The central part of the Menderes Massif also shows elevated heat flow values, the highest values (> 100 mW m(-2)) being in the northeastern part of the Gediz Graben near the Kula volcanic center. Moderate heat flow values of 55-70 mW m(-2) are observed in the eastern part of Canakkale, central part of BalA +/- kesir, northwest of Manisa, and northeast end of Bursa including Yalova. Some of the observed moderate values may be related to unconstrained near surface phenomena due to shallow depth of measurements. Towards the south of the study region, moderate heat flow values are also observed in Mugla. Previously reported regional heat flow values exceeding similar to 120 mW m(-2) is not observed in the region. The heat flow values reported in this study are comparable to the previously reported values in the Aegean Sea, as the two regions form the back-arc section of the Hellenic subduction zone.
Keywords: GEDIZ GRABEN; 2-STAGE EXTENSION; TURKEY; EVOLUTION; SYSTEM